Photoluminescence behavior of YPO4:Tb3+ crystallized in monoclinic, hexagonal or tetragonal phase obtained by hydrothermal process. (December 2016) - Garrido Hernández, A.; García Murillo, A.; Carrillo Romo, F. de J.; Boyer, D.; Potdevin, A.; Chadeyron, G.; Miranda, J. Reyes
Graphical abstract: Highlights: YPO4 nanoparticles were synthesized by hydrothermal process. Effects of varying pH, temperature and dopant concentration on morphology were studied. Crystalline structures of YPO4 depend on the pH and temperature of synthesis. Hexagonal phase of YPO4 :Tb 3+ powders is dependent on the terbium quantity and pH value. The morphology depends on the crystal structure. Abstract: The luminescent intensity of rare earth-doped lanthanide orthophosphates (LnPO4 :Re 3+ ) vary, depending on morphology and crystal structure. In this context, terbium-doped yttrium orthophosphate (YPO4 :Tb 3+ ) nanoparticles with different morphologies and crystalline structures were successfully obtained by hydrothermal process. The morphology and crystal structure were modified by varying the pH, temperature and dopant concentration. The YPO4 :Tb 3+ nanocrystals were characterized by XRD, FT-IR, SEM, TEM and photoluminescence. X-ray patterns show that monoclinic, hexagonal and tetragonal phases of YPO4 depend on the pH and temperature of synthesis; besides synthesis conditions, the hexagonal structure is influenced by the terbium concentration. The monoclinic phase is transformed into the tetragonal phase at synthesis temperatures higher than 100° C. Both structures, monoclinic and hexagonal, change to the tetragonal phase when subjected to heat treatment. According to SEM images, the morphology depends on the crystal structure. Finally, the photoluminescent properties of YPO4 :Tb 3+ with different crystal structures were investigated and compared.